GENETIC TRANSFORMATION AND REGENERATION OF TRANSGENIC PLANTS FROM COTYLEDON OF EUCALYPTUS UROPHYLLA VIA AGROBACTERIUM - Van Thang, Bui (Journal of Forestry Science and Technology, 2016)
A protocol of the Agrobacterium - mediated transformation of Eucalyptus urophylla cotyledon was successfully developed. The cotyledon explants from in vitro 7 day old seedlings were precultured for three days in dark on the induction medium MS* (reduced 1/3 total nitrogen content) supplemented with 1.0 mg/l benzylaminopurine (BAP), 0.5 mg/l naphthalene acetic acid (NAA), 100 ml/l coconut water, 20 g/l sucrose, 2.0 g/l phytagel, and 50 µM acetosyringone (AS). Those cotyledon explants were infected with Agrobacterium tumefaciens C58 strain that harbored the binary vector pBI21 carrying uidA and neomycin phosphotransferase II (nptII) genes for ten minutes, then co-cultured on the MS with 100 µM AS for 72 hours in dark. Subsequently, the infected cotyledon explants were washed off the Agrobacterium, and transferred to the MS supplemented with 400 mg/l cefotaxime (without kananamycin) for four days of culture. In the next step, those cotyledon explants were transferred to the selective MS supplemented with 400 mg/l cefotaxime and 150 mg/l kanamycin for three weeks of culture. After three passages on the selective medium, the kanamycin-resisted shoots were transferred to the rooting MS** (reduced 1/2 total nitrogen content) supplemented with 0.3 mg/l NAA, 0,2 mg/l Indolebutyric acid (IBA), 20 g/l sucrose, 8 g/l agar, 300 mg/l cefotaxime, and 75 mg/l kanamycin; the shoots were rooted after two week of culture. The rooted shoots (plantlets) on the selective medium which were transformed were detected by histochemical GUS assay and PCR with specific primers. Six plantlets of the 162 co-cultured explants were successfully genetically transformed. The frequency of genetic transformation using markers uidA and nptII for Eucalyptus urophylla was 3.7%. The developed protocol can be applied in successful transformation of the genes of interest into Eucalyptus urophylla.